2005
DOI: 10.1152/japplphysiol.00419.2005
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo microanalytical technique for measuring the local biochemical milieu of human skeletal muscle

Abstract: Myofascial pain associated with myofascial trigger points (MTrPs) is a common cause of nonarticular musculoskeletal pain. Although the presence of MTrPs can be determined by soft tissue palpation, little is known about the mechanisms and biochemical milieu associated with persistent muscle pain. A microanalytical system was developed to measure the in vivo biochemical milieu of muscle in near real time at the subnanogram level of concentration. The system includes a microdialysis needle capable of continuously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
340
2
38

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 588 publications
(397 citation statements)
references
References 23 publications
17
340
2
38
Order By: Relevance
“…Another possible explanation of our findings is that lower PPT values over a spontaneously painful human skeletal muscle presents significantly elevated levels of substance P, calcitonin gene-related peptide, bradykinin, tumor necrosis factor ␣, interleukin-1␤, serotonin, and norepinephrine versus nonpainful, healthy subjects (31). The concentration of selected inflammatory mediators, neuropeptides, cytokines and catecholamines also differ quantitatively from a remote, uninvolved site (32).…”
Section: Discussionmentioning
confidence: 73%
“…Another possible explanation of our findings is that lower PPT values over a spontaneously painful human skeletal muscle presents significantly elevated levels of substance P, calcitonin gene-related peptide, bradykinin, tumor necrosis factor ␣, interleukin-1␤, serotonin, and norepinephrine versus nonpainful, healthy subjects (31). The concentration of selected inflammatory mediators, neuropeptides, cytokines and catecholamines also differ quantitatively from a remote, uninvolved site (32).…”
Section: Discussionmentioning
confidence: 73%
“…[6][7][8] Eliciting LTRs can reduce concentrations of nociceptive chemicals, such as substance P and calcitonin gene-related peptide, found in the immediate vicinity of active TrPs. 9,10 Trigger point dry needling is commonly used in clinical practice by physiotherapists in conjunction with other physical therapy modalities. 1 In many countries, including Ireland, the United Kingdom, Canada, and Spain, TrP-DN has been recognized to fall within the scope of physiotherapy practice.…”
Section: Introductionmentioning
confidence: 99%
“…Ischaemia, energy crisis and contraction metabolites increase the local concentration of inflammatory and pain metabolites leading to the development of painful trigger points. Shah et al [38] found significantly increased concentrations of [H + ], bradykinin, calcitonin gene-related peptide, substance P, tumour necrosis factor-α, interleukin-1β, serotonin and norepinephrine in active TrPs only. SEA in TrPs was stated to be different from spontaneous activity of normal neuromuscular junctions: the electrical discharges occur with frequencies that are 10-1000 times that of normal miniature end plate potentials [39].…”
Section: Trigger Points Taut Bands and Pain Spotsmentioning
confidence: 99%
“…The situation may be different in experimental studies, where the function of acetylcholinesterase was blocked [41]. The findings of microdialysis of trigger points [38] can be explained by intrafusal microdialysis: a twitch elicited by insertion of the capillary needle may show a myotatic reflex by the activation of intrafusal 1a-afferents of the given muscle spindle. Taut bands may be the final result of sustained reflex activation of beta motor units by intrafusal II-, III-and IV-afferents [25,27,28].…”
Section: Trigger Points Taut Bands and Pain Spotsmentioning
confidence: 99%